2016
DOI: 10.18006/2016.4(5).519.524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the foliar application of humic acid on red bean cultivars (Phaseolus vulgaris L.)

Abstract: In order to evaluate the effect of foliar application of humic acid on yield and yield components of red bean cultivars this experiment was conducted at Agricultural Research Station of Arak in 2014. The experiment was in split plots Completely Randomized Block Design (CRBD) with three replications. Three level of humic acid i.e. 0, 1.5 and 3 liters per hectare in main plots and three cultivars of red bean i.e. Derakhshan, Goli and D81083 were in sub plots used as treatments. Results of study revealed that lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…Increasing pea yields as a result of using humic acids and compost tea may be attributed to enhancing the growth which mainly due to their high contents of organic and mineral substances with hormone-like activities through their involvement in photosynthesis, proteins synthesis and various enzymatic reactions (Atiyeh et al, 2002 andGad El-Hak et al, 2012). Similar increments in total yields were obtained by Mohajerani et al (2016) on beans, Shehata et al (2016) on lettuce and Yasir et al (2016) on cucumber. The data in Table 7 show that both of pod length and weight of 100 seeds of peas were non-significantly influenced by treatments in both seasons.…”
Section: Effect Of Bio Safe Compounds Resistance Inducers and Fungicsupporting
confidence: 78%
See 1 more Smart Citation
“…Increasing pea yields as a result of using humic acids and compost tea may be attributed to enhancing the growth which mainly due to their high contents of organic and mineral substances with hormone-like activities through their involvement in photosynthesis, proteins synthesis and various enzymatic reactions (Atiyeh et al, 2002 andGad El-Hak et al, 2012). Similar increments in total yields were obtained by Mohajerani et al (2016) on beans, Shehata et al (2016) on lettuce and Yasir et al (2016) on cucumber. The data in Table 7 show that both of pod length and weight of 100 seeds of peas were non-significantly influenced by treatments in both seasons.…”
Section: Effect Of Bio Safe Compounds Resistance Inducers and Fungicsupporting
confidence: 78%
“…They enhanced roots, leaves and shoots growth of many plants as well as stimulate nutrients uptake for major nutrients (Mohajerani et al, 2016). Similarly, Shehata et al (2016) and Yasir et al (2016) showed that HA increased fresh and dry weights of leaves, number of leaves, total yield and improved quality as well as chlorophyll and carotenoid contents of head lettuce and cucumber.…”
Section: Introductionmentioning
confidence: 94%
“…If the Ca/P ratio is low, calcium will be low and there will be high phosphorus intake which leads to calcium loss in the urine more than normal. If the Ca/P ratio of any food is above one that food is considered “good” and “poor” if the ratio is less that 0.5, Ca/P ratio above two helps to increase the absorption of calcium in the small intestine [35] . Sodium and potassium are required for the maintenance of osmotic balance of the body fluids, the pH of the body to regulate muscles and nerves irritability, control glucose absorption and enhance normal retention of protein during growth.…”
Section: Resultsmentioning
confidence: 99%
“…Foliar application of humic acid improve the plant growth, accumulated photosynthetic matters and biological yield of red bean (Mohajerani et al, 2016). Application of zinc and boron in accompanied with humic acid and compost can be an effective nutritional manipulation by fixing the recommended dose of NPK to successfully reduce the pest and disease incidence in rice-mustard cropping system (Roy et al, 2017).…”
Section: Effect Of Ha On Crop Productionmentioning
confidence: 99%